Analisis Keterampilan Jump Serve Bola Voli Pada Pemain Putra PERVOPA Patemon - Muhammad Rifantofana; Agung Wahyudi (Universitas Negeri Semarang, 2024)
The purpose of this study was to analyze the volleyball jump serve skills of male PERVOPA Patemon players which are analyzed from the starting phase to the landing phase so that they can improve the jump serve movement to make it more effective and efficient. This type of research uses quantitative descriptive. The sample was 5 PERVOPA Patemon athletes who used the jump serve technique. The instrument used is a video documentation of the jump serve skill test whose movements will be analyzed using kinovea series 0.8.15 software, and the results of the jump serve test with Serbian international players as a reference will be calculated. The results of the research show that the jump serve technical skills of junior athlete PERVOPA Patemon have not performed a series of jump serve movements optimally when compared to Serbian international players. This is because the series of movements carried out have not reached the optimal angle of the body segments. It can be concluded that the jump serve skills of PERVOPA players are still lacking, this is caused by a lack of starting distance, flexibility of body segments, ease of hand on the ball and bending of the knees when landing.